2022
DOI: 10.3390/en15051901
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Erosion Wear for Continuous Elbows in Different Directions

Abstract: The purpose of the present study is to simulate the continuous bend erosion process in different directions, using the dense discrete particle model (DDPM). The influence of the length of the straight pipe in the middle of the continuous bend is investigated. The Rosin–Rammler method is introduced to define the diameter distribution of erosion particles, which is theoretically closer to the actual engineering erosion situation. The numerical model is based on the Euler–Lagrange method, in which the continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The most severe erosion area is located near the outlet end of the elbow and the overall defect morphology is symmetrical about the center plane of the elbow, showing a parabolic shape [47,48]. Therefore, we used a handheld grinder to make oval-shaped pits to simulate the actual erosion area during the experiment.…”
Section: Experimental Programmentioning
confidence: 99%
“…The most severe erosion area is located near the outlet end of the elbow and the overall defect morphology is symmetrical about the center plane of the elbow, showing a parabolic shape [47,48]. Therefore, we used a handheld grinder to make oval-shaped pits to simulate the actual erosion area during the experiment.…”
Section: Experimental Programmentioning
confidence: 99%
“…Finnie [12] demonstrated that the erosion rate is proportional to the square of the particle velocity. Li et al [13] simulated the continuous bend erosion process in various directions using the dense discrete particle model. They conducted numerical simulations on seven continuous elbows with different orientations, considering straight pipe lengths and particle sizes as variables.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis presented here adopts the distribution of dust particles according to the Rosin-Ramler model, often used in studies of dusting processes. This distribution is used to describe the diameter distribution of dust particles (materials) from processes such as grinding, milling, mincing and crushing, as well as for the diameter distribution of particles formed in other processes [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%